2017
DOI: 10.1515/johr-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Proliferation and Cryoconservation of Banana and Plantain Elite Clones

Abstract: Agriculture and modern biotechnology are increasingly becoming interdependent, and many new techniques have brought new opportunities for enhancing production and marketing. Germplasm storage is an alternative for the conservation of plant genetic diversity, contributing to the improvement and maintenance of propagation programs for species of interest. In this work, banana corms were collected as plant material from relatively young commercial plantations of three different cultivars: 'Williams', Valery (AAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The number of proliferating buds increased by the fifth subculture with the number of buds more than doubled in Litete (11.2) while the number of buds for Libanga Likale increased less drastically (8.6). Reyes et al (2017) found in vitro proliferation rates of 1.95-2.20 in plantains, while Korneva et al (2013) found a 0.8 proliferation rate for plantain and 1.86 for banana. Our results are also in line with Dhed'a (1992), who showed that 10 μM BAP increased the proliferation rates in in vitro with 3.5 for the plantain cultivar Three Hand Planty (Musa AAB) with 18.6, 12.4 and 21.4 for the cooking banana cultivars Bluggoe, Cardaba and Saba (Musa ABB) and 7.1 for the dessert banana cutivar Yangambi Km5 (Musa AAA).…”
Section: Discussionmentioning
confidence: 97%
“…The number of proliferating buds increased by the fifth subculture with the number of buds more than doubled in Litete (11.2) while the number of buds for Libanga Likale increased less drastically (8.6). Reyes et al (2017) found in vitro proliferation rates of 1.95-2.20 in plantains, while Korneva et al (2013) found a 0.8 proliferation rate for plantain and 1.86 for banana. Our results are also in line with Dhed'a (1992), who showed that 10 μM BAP increased the proliferation rates in in vitro with 3.5 for the plantain cultivar Three Hand Planty (Musa AAB) with 18.6, 12.4 and 21.4 for the cooking banana cultivars Bluggoe, Cardaba and Saba (Musa ABB) and 7.1 for the dessert banana cutivar Yangambi Km5 (Musa AAA).…”
Section: Discussionmentioning
confidence: 97%
“…In vitro storage with minimal growth by encapsulation using sodium alginate in Murashige and Skoogs Medium is necessary to reduce the constraints of banana preservation. Sodium alginate and calcium chloride are the best combinations for encapsulation explants because these ions are non-destructive, inexpensive, easy to use, and result in the high conversion of encapsulated embryos to plants (Sharma et al 2012a;Reyes et al 2017;Phanomchai et al 2022). It is also cost-effective for clonal propagation systems (Ahmad et al 2012).…”
Section: In Vitro Medium-term Storage Of Banana Using Alginate-encaps...mentioning
confidence: 99%